The Role of higher education student volunteerism in community service through student citizenship behavior - Nur Syifa Izzati Muhamad Zuki,; Nuruljannah Ahmad Puzi,; Meor Muhammad Afif Aiman Abu Bakar,; Abu Bakar Ahmad Mansor, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The role of student volunteerism within higher education institutions in community service is interconnected with student citizenship behaviour. Student volunteerism is essential in promoting citizenship behaviour and generating beneficial outcomes in local communities. However, there is little emphasis and inconsistent research findings within a research field. Therefore, this review paper explores how student volunteerism will contribute to community service programs by fostering citizenship behaviour. This recent study will provide a review of the literature on the role of student volunteerism and its distinction with citizenship behaviour as well as conceptual in terms of student citizenship behaviour, and to understand its challenge and issues pertaining to student volunteers in community service. Data has been sourced from a review of literature found in journals, articles, and research projects. This study includes an initial analysis of existing literature, which is followed by a content analysis that specifically delves into the development of the concept and the functions of student citizenship behaviour and student volunteerism within community service, aiming to support and maintain their engagement. The future implications of this research may involve aiding educational institutions, communities, and relevant organisations in enhancing volunteerism among higher education students.